The Principle of Asymmetry Aesthetic in Cinematography - Limano, Ferric (Humaniora, 2018)
The research showed the principle of asymmetry having a grasp of aesthetic in cinematography. It was needed the understanding of conceptual tools in filming, not only the physical tools. With this principle, the research presented the recommendations in practice that could be applied better in visual for the audience.Methods used in this research was qualitative descriptive. There was a connection of the principle asymmetry with object research (conceptual tools in cinematography) included; frame, light and color, lens, movement, texture, establishing, and point of view with comparison with symmetry principle, then simulate with 3D (three dimensional) editor. The result of this research is people can apply this principle to experience the constant that added the aesthetic in the film with hope to give advantages to the Indonesian movie industry.